2019
DOI: 10.1002/slct.201900088
|View full text |Cite
|
Sign up to set email alerts
|

First Report on 3‐(3‐oxoaryl) Indole Derivatives as Anticancer Agents: Microwave Assisted Synthesis, In Vitro Screening and Molecular Docking Studies

Abstract: In this study ZrCl4 was identified as an efficient Lewis acid catalyst for the synthesis of 3‐(3‐oxoaryl) indole derivatives via microwave assisted Michael addition of 2‐phenylindole with chalcones under solvent‐free condition. The reaction proceeds smoothly with high efficiency under green reaction condition to afford a range of 3‐(3‐oxoaryl) indole derivatives exclusively within a short period of time in excellent yields. The synthesized compounds have shown promising in vitro anticancer activity against mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The molecular docking studies showed a greater degree affinity of these compounds over colchicine in the active site of CBS. [64] 2.17 | Indole-based [1,2,4]triazolo [4,3-a]…”
Section: -Phenyl-1h-indole-2-carbohydrazide Derivativesmentioning
confidence: 99%
“…The molecular docking studies showed a greater degree affinity of these compounds over colchicine in the active site of CBS. [64] 2.17 | Indole-based [1,2,4]triazolo [4,3-a]…”
Section: -Phenyl-1h-indole-2-carbohydrazide Derivativesmentioning
confidence: 99%
“…The reactions were tested with and without the use of solvent, obtaining comparable results ( Kalluraya et al, 2018 ). In the same way, a new protocol, for the synthesis of 3-(3-oxoaryl)indole derivatives, was developed through a microwave-assisted Michael addition of the appropriate chalcone derivatives using commercially available and non-toxic catalyst under solvent-free conditions ( Figure 8C ) ( Patel et al, 2019 ). 1,5-Benzodiazepine derivatives were synthesized with good yields and without the need for column chromatography purification, starting from differently substituted chalcones and 2-aminoaniline dissolved in piperidine and ethanol with the aid of a domestic microwave ( Shetye and Pawar, 2017 ).…”
Section: 1 Ultrasound Chemistrymentioning
confidence: 99%
“…68 Gayen and co-workers exploited Michael addition reaction and thereby disclosed an effective microwave assisted, solvent-free methodology for 3-(3-oxoaryl)indole derivatives from 2-phenylindole and chalcones in the presence of Lewis catalyst, ZrCl4 (Scheme 38). 69 In the optimized reaction condition, 15 mol% of ZrCl4 was used as the suitable catalyst under microwave radiation power of 280W. The reaction was more facile with chalcones bearing electron-withdrawing group compared to electron-donating ones.…”
Section: Scheme 29mentioning
confidence: 99%